Financial Ratio Analysis for Strategic Decision-Making in the Football Industry: A Case Study of PT Bali Bintang Sejahtera (2019–2023) - Rangga Eka Saputra; Lia Nirawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the financial performance of PT Bali Bintang Sejahtera Tbk for the 2019–2023 period based on liquidity, solvency, and profitability ratios to evaluate financial stability and the effectiveness of the club's business strategies within the football industry. This research utilizes secondary time-series data obtained from annual financial reports published on the Indonesia Stock Exchange (BEI). The analysis results indicate that PT Bali Bintang Sejahtera Tbk exhibits very high liquidity, with a current ratio of 875.19%, a quick ratio of 257.55%, and a cash ratio of 257.55%. In terms of solvency, the debt-to-asset ratio of 10.78% and the debt-to-equity ratio of 12.19% reflect a low dependency on debt. However, profitability still requires improvement, with a return on assets (ROA) of 5.75% and a return on equity (ROE) of 6.28%. This study contributes to a better understanding of financial performance in football clubs. Practically, the findings serve as a reference for investors, creditors, and club management in making strategic decisions related to investment, financing, and asset management to enhance profitability and competitiveness.